Mental distress and incident functional disability among a rural ageing population in South Africa - Pengpid S. (2023)
Objectives: The aim of the study was to investigate the association between mental symptoms and incident functional disability among middle-age and older adults in South Africa. Methods: Longitudinal data from two consecutive population surveys (2014/2015–2018/2019) in Agincourt, South Africa, were analysed. Results: In total, 298 of 3813 participants without functional disability in wave 1 (8.8%) had functional disability in wave 2. The prevalence of baseline functional disability was 9.1%. In the fully adjusted models for people without functional disability at baseline, depressive symptoms (AOR: 1.74, 95% CI: 1.08–2.80) among men and lower life satisfaction among men (AOR: 0.86, 95% CI: 0.80–0.93) and among women (AOR: 0.90, 95% CI: 0.83–0.98) increased the odds of incident functional disability. Posttraumatic stress disorder symptoms, poor sleep quality, restless sleep, and loneliness were not significantly associated with incident functional disability. Conclusions: Depressive symptoms among men and lower life satisfaction among both sexes were independently associated with incident functional disability in ageing rural South Africans.